Issue Information TOC. (14th June 2019) - Unknown
Abstract : Cover : In Singh et al. (https://doi.org/10.1002/cpim.70 ), Hematoxylin‐ and eosin‐stained sections of ear skin. Hematoxylin‐ and eosin‐stained sections of untreated (left), rIL‐23‐treated (middle), and Aldara/IMQ‐treated (right) ears. Acanthosis, thickening of the epidermis; hyperkeratosis, thickening of the stratum corneum; parakeratosis, retention of nucleated keratinocytes in the stratum corneum; micro‐abscesses, neutrophil aggregates in the stratum corneum can be observed in these images. See e71.